Pengembangan history e-magazine (histoemag) berbasis koleksi museum Kabupaten Pasuruan kelas X IBB SMAN 1 Bangil - Muntiani Muntiani; Slamet Sujud Purnawan Jati; Ulfatun Nafi’ah (Universitas Negeri Malang, 2022)
The purpose of writing this article is to produce a product and to find out the effectiveness of using Adobe Flash-based History e-magazine (Histoemag) teaching materials for Hindu-Buddhist historical heritage materials in the Pasuruan Regency Museum Collection for class X IBB SMAN 1 Bangil students. Departing from the potential and problems found, namely the lack of use of innovative teaching materials in history learning, the researchers developed teaching materials in the form of History electronic magazine (Histoemag). The research used to develop this product uses a research and development model according to Sugiyono with 10 stages consisting of: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trial, 7) product revision, 8) use trial, (9) product revision, and 10) mass production. The research and development of this product produces teaching materials in the form of historical electronic magazines containing Hindu-Buddhist historical heritage materials which are packaged into three parts accompanied by pictures, videos, game rubrics (crossword puzzles) and practice questions (quizzes) that support the delivery of material in teaching materials. The results of the validation of the material experts were 92.85 percent (very valid), 98.21 percent of the teaching materials experts (very valid), 91.83 percent of the small group trial results (very effective) and the large group trial results obtained 94.60 percent (very effective). Based on the results obtained, it shows that the History e-magazine teaching materials based on Adobe Flash are declared to be very valid and very effective by meeting the criteria of being very worthy as teaching materials. Tujuan penulisan artikel ini menghasilkan produk serta mengetahui keefektifan penggunaan bahan ajar History e-magazine (Histoemag) berbasis Adobe Flash materi peninggalan sejarah Hindu-Buddha pada Koleksi Museum Kabupaten Pasuruan untuk siswa kelas X IBB SMAN 1 Bangil. Berangkat dari potensi dan masalah yang ditemukan yakni minimnya penggunaan bahan ajar inovatif dalam pembelajaran sejarah, peneliti mengembangkan bahan ajar berupa History electronic magazine (Histoemag). Penelitian yang digunakan untuk mengembangkan produk ini menggunakan model penelitian dan pengembangan menurut Sugiyono dengan 10 tahapan terdiri dari: 1) potensi dan masalah, 2) pengumpulan data, 3) desain produk, 4) validasi desain, 5) revisi desain, 6) uji coba produk, 7) revisi produk, 8) uji coba pemakaian, (9) revisi produk, dan 10) produksi massal. Penelitian dan pengembangan produk ini menghasilkan bahan ajar berbentuk majalah elektronik sejarah memuat materi peninggalan sejarah Hindu-Buddha yang dikemas menjadi tiga bagian disertai gambar, video, rubrik game (teka-teki silang) dan latihan soal (kuis) yang dapat mendukung penyampaian materi dalam bahan ajar. Adapun hasil validasi ahli materi diperoleh sebesar 92,85 persen (sangat valid), 98,21 persen dari ahli bahan ajar (sangat valid), 91,83 persen dari hasil uji coba kelompok kecil (sangat efektif) dan hasil uji coba kelompok besar memperoleh sebesar 94,60 persen (sangat efektif). Berdasarkan hasil yang diperoleh menunjukkan bahwa bahan ajar History e-magazine berbasis Adobe Flash dinyatakan sangat valid dan sangat efektif dengan memenuhi kriteria sangat layak sebagai bahan ajar.